(untitled) (Al-Quds Journal for Natural Sciences, 2021)
Increasing evidence has indicated that the non-coding RNA molecules play central roles in almost all biological processes and many pathological conditions including carcinogenesis. This review focuses on the pathological tumorigenic role of the first discovered long non-coding RNA gene called H19 and its pivotal contribution to the cancer axis of evil. H19 RNA utilizes a variety of mechanisms to perform its pathological function. Some key unanswered questions are presented by the end. Understanding the H19 RNA mechanisms of action will shed light into the class of long non-coding RNA which contains thousands of members mostly with unknown function and will help in delineating the pathological role played by at least some of them.